2009
DOI: 10.1007/s12253-009-9227-0
|View full text |Cite
|
Sign up to set email alerts
|

Per2 Inhibits K562 Leukemia Cell Growth In Vitro and In Vivo Through Cell Cycle Arrest and Apoptosis Induction

Abstract: Per2 regulates other molecular and biochemical processes beyond their established role in the regulation of the mammalian circadian clock, herein we investigated the growth inhibiting potential of Per2 in human K562 leukemia cells and the underlying mechanisms. The results showed that over-expression of Per2 induced not only cell cycle arrest at G2/M phase but also an increase in apoptosis, which was confirmed by characteristic morphological changes, FCM and evident DNA fragmentation. Further experiments confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 30 publications
7
55
0
1
Order By: Relevance
“…We have investigated the role of PER2 in glioma. Evidence from initial research implicated PER2 as a regulator of the circadian clock [14,[23][24][25]; more recently evidence has expanded on the function of PER2 function to include the promotion of apoptosis in cancer [9,11]. We hypothesized that PER2 is also a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have investigated the role of PER2 in glioma. Evidence from initial research implicated PER2 as a regulator of the circadian clock [14,[23][24][25]; more recently evidence has expanded on the function of PER2 function to include the promotion of apoptosis in cancer [9,11]. We hypothesized that PER2 is also a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…After comprehensively surveying the links between PER2 and TP53 in previous reports [2,4,[9][10][11][12][13][14][15], we selected wild-type TP53 human U343 glioma cells, then RNA interference technology and shRNA-lentivirus were used to downregulate PER2. However, we found that following treatment with 6 mV, 100cGy of X-ray irradiation, DNA damage was observed in both two groups after 24 h, and shRNA-PER2-transfected cells showed more serious DNA tailing phenomena and significantly increased death rate compared with control cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C-MYC directly blocks cyclin D1 activity, which is a roadblock for G1/S phase transition in the cell cycle. Overexpression of Per2 concomitantly leads to cell cycle arrest in certain cancer cell lines and pushes these cells into apoptosis (Hua et al 2006 ;Oda et al 2009 ;Sun et al 2010 ). Recently, a relatively new clock player termed NONO has also been implicated in cell cycle regulation.…”
Section: Role Of the Circadian Clock In Cell Cyclementioning
confidence: 99%